INFLUENCE OF LEADERSHIP, AND WORK CULTURE ORGANIZATIONAL CLIMATE ON EMPLOYEE PERFORMANCE REGIONAL PERSONNEL AGENCY AND HUMAN RESOURCE DEVELOPMENT BOVEN DIGOEL DISTRICT - Eki Sarifin (Scientia Integritas Utama, 2022)
This study aims to determine the effect of leadership, work culture and organizational climate on the performance of employees of the Regional Personnel Agency and Human Resource Development Boven Digoel Regency. This research is a quantitative research, the data used is primary data, namely data obtained from distributing questionnaires to the research object. The population of this study were all employees of the Regional Personnel Agency and Human Resources Development Boven Digoel Regency. The sampling technique used purposive sampling with a total sample of 35 respondents. In analyzing the research data using the SPSS version 26 application. The results showed that (1) leadership has a positive and significant effect on work culture; (2) Leadership has a positive and significant effect on organizational climate; (3) Leadership has a positive and significant effect on employee performance; (4) Work culture has a positive and significant effect on employee performance; (5) Organizational climate has a positive and significant effect on employee performance; (6) Leadership has a positive and significant effect on employee performance through work culture; and (7) Leadership has a positive and significant effect on employee performance through organizational climate at the Regional Personnel Agency and Human Resource Development Boven Digoel Regency. (5) Organizational climate has a positive and significant effect on employee performance; (6) Leadership has a positive and significant effect on employee performance through work culture; and (7) Leadership has a positive and significant effect on employee performance through organizational climate at the Regional Personnel Agency and Human Resource Development Boven Digoel Regency. (5) Organizational climate has a positive and significant effect on employee performance; (6) Leadership has a positive and significant effect on employee performance through work culture; and (7) Leadership has a positive and significant effect on employee performance through organizational climate at the Regional Personnel Agency and Human Resource Development Boven Digoel Regency.